(untitled) (Research, Society and Development, 2025)
The objective of this article is to present an analysis of the scientific literature on the application of bioethical principles in the practice of orthodontics, as well as the trends and challenges faced by orthodontists today. Orthodontics is the branch of dentistry focused on the correction of malocclusions to improve both masticatory function and facial aesthetics. Orthodontics is the branch of dentistry focused on correcting malocclusions to improve both chewing function and facial aesthetics. However, the adoption of new technologies and the growing demand for aesthetic treatments pose ethical challenges in orthodontic practice. Through a descriptive methodology, continuous training in bioethics and the development of public policies are key to facing emerging challenges. Integrating bioethics into orthodontics ensures respect for patient rights and clinical excellence. Professional responsibility and the promotion of equity in access to orthodontic care are becoming relevant in the face of technological transformations and current aesthetic demands.